Comparison of incidence trends of early-onset and late-onset type 2 diabetes in the Asia-Pacific region, 1990-2021: a join point regression analysis based on the global burden of disease study 2021 - Lin, Chenying; An, Haohua; Lin, Jingna; Cao, Yuejuan; Yang, Zhen (Frontiers in Endocrinology, 2025)
IntroductionThis study evaluated the incidence trends of early-onset (diagnosed at ages 15-39) and late-onset (diagnosed at age 40 and above) type 2 diabetes mellitus (T2DM) in the Asia-Pacific region, including the World Health Organization (WHO) South-East Asia Region (SEARO) and Western Pacific Region (WPRO), and assessed the impact of the COVID-19 pandemic.MethodsUsing data from the Global Burden of Diseases Study (GBD) 2021, we analyzed trends in age-standardized incidence rate (ASIR) using Join point regression to determine annual percentage change (APC). To assess the pandemic’s impact, we calculated excess incidence for 2020 and 2021 by subtracting predicted ASIR from observed ASIR.ResultsIn recent years, particularly during the COVID-19 pandemic, the ASIR for early-onset T2DM in the Asia-Pacific region accelerated significantly. SEARO’s APC rose from 2.24% between 2011-2019 to 5.45% between 2019-2021. Similarly, WPRO’s APC increased from 1.71% between 1999-2017 to 5.01% between 2017-2021. In 2021, the ASIR for early-onset T2DM was 269.6 per 100,000 in WPRO and 248.4 per 100,000 in SEARO. Conversely, late-onset T2DM ASIR growth in SEARO slowed after 2017 (APC 1.92% for 2005-2017 vs. 1.04% for 2017-2021), while WPRO saw a decline (APC 1.06% for 2007-2017 vs. -1.10% for 2017-2021). During the COVID-19 pandemic in 2020 and 2021, the observed ASIR of early-onset T2DM in the Asia-Pacific region exceeded historical predictions, showing a positive excess in ASIR.ConclusionsThis study reveals a significant recent increase in early-onset T2DM incidence in the Asia-Pacific region, highlighting the need for targeted public health interventions.